Parallel Trading by Institutional Investors - Kraus, Alan; Stoll, Hans R. (Journal of Financial and Quantitative Analysis, 1972)
A belief frequently expressed by observers of the stock market is that groups of institutions tend to trade in the same way at the same time. Two expressions of this belief follow:Frequently reference is made to the ‘impact’ of institutional investors on the stock market. Apparently it is worrisome to the observers of the markets to find that we tend to buy and sell somewhat in unison.